A critical appraisal of the role of intracellular Ca2+-signaling pathways in Kawasaki disease. (May 2018) - Bijnens, Jeroen; Missiaen, Ludwig; Bultynck, Geert; Parys, Jan B.
Graphical abstract: Highlights: Kawasaki disease is a multi-systemic vasculitis of unknown origin. Some genetic aberrances are located in genes linked with Ca 2+ signaling. We review the role of abnormal Ca 2+ signaling in the pathogenesis of the disease. Abstract: Kawasaki disease is a multi-systemic vasculitis that generally occurs in children and that can lead to coronary artery lesions. Recent studies showed that Kawasaki disease has an important genetic component. In this review, we discuss the single-nucleotide polymorphisms in the genes encoding proteins with a role in intracellular Ca 2+ signaling: inositol 1, 4, 5-trisphosphate 3-kinase C, caspase-3, the store-operated Ca 2+ -entry channel ORAI1, the type-3 inositol 1, 4, 5-trisphosphate receptor, the Na + /Ca 2+ exchanger 1, and phospholipase Cß4 and Cß1. An increase of the free cytosolic Ca 2+ concentration is proposed to be a major factor in susceptibility to Kawasaki disease and disease outcome, but only for polymorphisms in the genes encoding the inositol 1, 4, 5-trisphosphate 3-kinase C and the Na + /Ca 2+ exchanger 1, the free cytosolic Ca 2+ concentration was actually measured and shown to be increased. Excessive cytosolic Ca 2+ signaling can result in hyperactive calcineurin in T cells with an overstimulated nuclear factor of activated T cells pathway, in hypersecretion of interleukin-1ß and tumor necrosis factor-α by monocytes/macrophages, in increased urotensin-2 signaling, and in an overactivation of vascular endothelial cells.